Investigation into the failure of hot forming tools and their tribological behaviour - Englund, David; Forsström, Dan (2010)
As hot metal forming processes are becoming more and more popular, especially in the automotive industry, the need for a better understanding about the tribological behaviour of tool and workpiece is increasing. Ultimately the enhanced knowledge should lead to better quality of the produced parts as well as improved process economy through reduced maintenance and longer life of the tools. This masters’ thesis has been carried out at the Division of Machine Elements at Luleå University of Technology as a part of an ongoing project. The aim of this work was to analyse the failure mechanisms of real hot forming tools and also to investigate the influence of contact pressure and tool surface roughness on the tribological behaviour of tool steels and high strength boron steel at elevated temperatures. The project has been carried out in cooperation with Accra Teknik AB, a manufacturer of hardened boron steel components through roll forming and form fixture hardening. To perform the failure analysis, a Wyko 1100NT optical surface profiler and SEM/EDS have been used to analyse the surfaces. Microhardness measurements and microstructural investigations were also carried out. To study the influence of contact pressure and surface roughness on friction and wear at elevated temperature, a high-temperature pin-on-disc tribometer was used. The results show that the two tools (Stützrohr and A76) seem to experience similar damage mechanism with subsurface initiated cracks caused by thermal cycling. The tool Stützrohr has a lower hardness than what is expected in the bulk. Tool A76 suffers from quite severe corrosive wear as a result of exposure to cyclic heating in presence of water. A strong gradient between the nitrided layer and the bulk material will make cracks propagate faster and this has been especially found in case of Stützrohr. Steadier friction in case of rougher tool surface is caused by formation of compacted layers of (Fe and O) oxidized wear particles. The rougher surface will generate more particles initially ...